1993
DOI: 10.1007/bf00165391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long term caffeine treatment on A1 and A2 adenosine receptor binding and on mRNA levels in rat brain

Abstract: The effect of long-term oral treatment with caffeine on A1 and A2 receptors in the rat brain was studied. Caffeine was added to the drinking water and the animals were sacrificed after a 12 day treatment period. The plasma caffeine concentration was close to 100 microM. A1 receptors were studied using quantitative autoradiography with [3H]cyclohexyladenosine (CHA). Caffeine treatment increased the number of A1 receptors in the CA3 subfield of the hippocampus from 337 to 393 fmol/mg with no change in KD (0.692 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
88
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 131 publications
(98 citation statements)
references
References 36 publications
8
88
2
Order By: Relevance
“…We and others have reported that a single injection of caffeine at doses between 50 and 100 mg/kg can upregulate expression of mRNA for the immediate early genes c-fos, jun B and c-&n (Nakajima et al, 1989;Johansson et al, 1993a;Svenningsson et al, 1995). This induction is followed by increased levels of mRNA for enkephalin and dynorphin in the same regions (Svenningsson et al, 1995, and own unpublished observations).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…We and others have reported that a single injection of caffeine at doses between 50 and 100 mg/kg can upregulate expression of mRNA for the immediate early genes c-fos, jun B and c-&n (Nakajima et al, 1989;Johansson et al, 1993a;Svenningsson et al, 1995). This induction is followed by increased levels of mRNA for enkephalin and dynorphin in the same regions (Svenningsson et al, 1995, and own unpublished observations).…”
Section: Discussionmentioning
confidence: 66%
“…It is important to point out that, in contrast to the decrease in the expression of immediate early genes seen after low doses, which occurs mainly in striatopallidal neurons, the increase after higher doses occurs in both types of medium-sized spiny neurons (Johansson et al, 1993a;Svenningsson et al, 1995; this study). We recently found an inhibition of the caffeine-induced expression of mRNA for NGFI-A, and c-fos in caudate-putamen following pretreatment with NMDA receptor antagonists (Svenningsson et al, 1996).…”
Section: Gaba Releasementioning
confidence: 67%
See 2 more Smart Citations
“…Adenosine A 1 receptors (A 1 Rs) are abundant in brain and a large proportion of these receptors are found on glutamatergic nerve endings, where they regulate transmitter release (Fredholm and Dunwiddie, 1988;Lupica et al, 1992;Johansson et al, 1993;Dunwiddie and Masino, 2001). The hippocampal formation is enriched with A 1 Rs (Fastbom et al, 1987;Svenningsson et al, 1997) and these receptors may be involved in the development and consolidation of longterm potentiation (LTP) (Arai et al, 1990;de Mendonca and Ribeiro, 1990;Alzheimer et al, 1991;Forghani and Krnjevic, 1995) and in induction of long-term depression (LTD) (de Mendonca et al, 1997;Bon and Garthwaite, 2002;Moore et al, 2003).…”
Section: Introductionmentioning
confidence: 99%